2014
DOI: 10.3892/ijo.2014.2461
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A, a natural chalconoid isolated from Glycyrrhiza inflata root, induces apoptosis via Sp1 and Sp1 regulatory proteins in oral squamous cell carcinoma

Abstract: Abstract. Licochalcone A (LCA), a chalconoid derived from root of Glycyrrhiza inflata, has been known to possess a wide range of biological functions such as antitumor, antiangiogenesis, antiparasitic, anti-oxidant, antibacterial and anti-inflammatory effects. However, the anticancer effects of LCA on oral squamous cell carcinoma (OSCC) have not been reported. Our data showed that LCA inhibited OSCC cell (HN22 and HSC4) growth in a concentration-and timedependent manner. Mechanistically, it was mediated via do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…A number of studies have reported that Sp1 is highly expressed in a variety of human tumors and that the use of natural compounds may be used to inhibit Sp1 expression in cancer (33). The effectiveness of anticancer agents is closely dependent on apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported that Sp1 is highly expressed in a variety of human tumors and that the use of natural compounds may be used to inhibit Sp1 expression in cancer (33). The effectiveness of anticancer agents is closely dependent on apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%
“…Sp1 is a transcription factor that modulates cell cycle regulation, anti-proliferative, and apoptosis cell death by regulating the promoter of target genes (14,32). Moreover, Sp1 regulates expression of many proteins such as p21, p27, cyclin D1, Mcl-1 and survivin (33). Among a variety of genes involved, in this experiment, cyclin D1, Mcl-1 and survivin were investigated.…”
Section: Manu a Modulates Sp1 And Sp1-regulated Proteins In The Maligmentioning
confidence: 99%
“…Previous studies on the development of chemotherapeutic agents have been focused on inducing cancer-specific cell death through the modulation of apoptosis, or programmed cell death. Furthermore, to overcome the side effects of current chemotherapeutic agents, studies have focused on the anti-cancer activity of natural compounds purified from herbal plants (7,(11)(12)(13)(14)(15). As a result of these studies, the US Food and Drug Administration approved the clinical use of a medicinal herbal plant-derived natural compound with anti-cancer activity for cancer therapy (16).…”
Section: Licochalcone-e Induces Caspase-dependent Death Of Human Pharmentioning
confidence: 99%
“…Licorice inhibits metastasis (18), has anti-proliferative properties (19), increases apoptosis and may cause cell cycle arrest (14). Recently, the authors demonstrated that licochalcone-A, a natural phenolic chalconoid purified from licorice (15), induces caspase-dependent apoptotic FaDu cell death through the extrinsic and intrinsic apoptotic signaling pathways.…”
Section: Licochalcone-e Induces Caspase-dependent Death Of Human Pharmentioning
confidence: 99%
“…Licochalcone A, an anti-inflammatory [1][2][3][4], immunomodulatory [5,6], and antimicrobial [3,5,[7][8][9] polyphenol extracted from Glycyrrhiza inflata [1][2][3]10], triggers apoptosis or inhibits proliferation and migration of tumor cells [11], including those of cervical cancer [12], oral squamous carcinoma [7,9,[13][14][15], esophageal carcinoma [16], gastric cancer [4,17,18], hepatocellular carcinoma [2,19], malignant pleural mesothelioma [20], bladder determined photometrically at 405 nm. The absorption of the supernatant of erythrocytes lysed in distilled water was defined as 100% hemolysis.…”
Section: Introductionmentioning
confidence: 99%